Estudo etnobotânico de plantas medicinais de Lavras e região: caracterização química e potencialidades biológicas dos óleos essenciais - Rezende, Danúbia Aparecida de Carvalho Selvati (2016)
The use of plants for medicine is common in Brazilian communities and has currently been gaining ground. Ethnobotanical studies show promise because they furnish valuable information about medicinal plants. Knowledge is transmitted by successive generations. The objectives of this study were to survey five plants most used by residents of Lavras and the region using a questionnaire, to extract and chemically characterize the essential oils of these plants and to determine the antioxidant and antibacterial activities, as well as their catalytic action, inhibitory activity against phospholipase and hemolytic activities. Essential oils were extracted by hydrodistillation using a modified Clevenger apparatus over a two-hour period. The oils were characterized chemically and quantified by GC-MS and GC-FID. The antioxidant activity was determined using the method of capture of the DPPH (2,2-diphenyl-1-picryl-hidrazila) radical, the oxidation of the β-carotene/linoleic acid system, the capture of the ABTS radical, the hydroxyl method, determination of reducing power and by reduction of molybdenum. Evaluation of antibacterial activity was performed by well diffusion in agar using Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, Salmonella Choleraesuis and Pseudomonas aeruginosa. The hemolytic phospholipase activities and were performed using Petri dishes containing agar gel and prepared human blood erythrocytes. To determine the phospholipase activity, the erythrocytes were replaced by egg yolk. The principal compounds in the essential oil from Mentha piperita were determined by gas chromatography to be carvone (84.3%) and limonene (10.9%); from Cymbopogon citratus, geranial (47.7%), neral (35.4%) and myrcene (8.5%); from Rosmarinus officinalis, 1,8-cineole (62.3%), camphor (17.3%) and α-pinene (9.1%); from Peumus boldus, α-terpinila (61.99%), p-cymene (15.5%), 1,8-cineole (10.6%), ascaridol (2.7%) and terpinen-4-ol (2.03%); from Foeniculum vulgare, methyl chavicol (89.5%), limonene (6.15%) and fenchone (3.80%). The highest antioxidant activity when evaluated by the hydroxyl test for all the essential oils. Only the essential oils from C. citratus and P. boldus presented significant activity in the molybdenum reduction method. In other methods, no significant antioxidant activity was observed for any of the essential oils. The lowest minimum inhibitory concentration (MIC) against Gram-negative and Gram-positive bacteria was observed for the essential oil from C. citratus. Inhibition of protease activity and partial inhibition of phospholipase A2 were observed for the essential oil from R. oficinalis. The oils from M. piperita and F. vulgare only inhibited proteases in the hemolytic activity test. C. citratus oil induced hemolysis, and the essential oil from P. boldus induced hemolysis and potentiated proteases.